2019
DOI: 10.1590/2317-1782/20182018183
|View full text |Cite
|
Sign up to set email alerts
|

Perfil miofuncional orofacial de pacientes com distúrbios do sono: relação com resultado da polissonografia

Abstract: RESUMO Objetivo Este trabalho se propõe a caracterizar o perfil miofuncional orofacial de pacientes com distúrbios do sono e relacionar esses com a gravidade do resultado da polissonografia. Método Estudo transversal, de campo, realizado com pacientes encaminhados para polissonografia, com amostra aleatória, composta por pacientes adultos, de ambos os gêneros, com queixa de ronco e que não estivessem recebendo alguma forma de tratamento para o distúrbio do sono. Foi realizada avaliação fonoaudiológica antrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
5
0
2
Order By: Relevance
“…The tendency of orofacial myofunctional changes in individuals with OSA has been demonstrated in another study, revealing that the greater the degree of structural impairment, the greater the severity of the disease 18 .…”
Section: Discussionmentioning
confidence: 80%
“…The tendency of orofacial myofunctional changes in individuals with OSA has been demonstrated in another study, revealing that the greater the degree of structural impairment, the greater the severity of the disease 18 .…”
Section: Discussionmentioning
confidence: 80%
“…Thus, a lower AHI would correspond to better results in rehabilitation, with favorable clinical outcomes. Researchers have found that the greater the degree of severity of apnea, the greater the degree of impairment of orofacial structures [ 37 ]. Accordingly, our results showed a trend, albeit without statistical significance, that individuals who did not show improvement in the degree of pharyngeal residue after swallowing therapy program exhibited higher AHI and higher likelihood of using CPAP.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is due to routine episodes of partial or total interruption of airflow in the upper respiratory tract caused by an anatomical obstruction in pharyngeal lymphoid tissue, making it collapse during sleep (2) . In children, its main causes include hypertrophy of pharyngeal and palatine tonsils, obesity/overweight, neuromotor diseases, and syndromes or changes related to the craniofacial complex (1)(2)(3)(4) . These aspects can impair children's global development, especially at school age when it is difficult to establish a sleep routine, compromising their weight, craniofacial, cardiopulmonary, neuropsychomotor, and behavioral growth, besides excessive daytime sleepiness and other disorders and habits unfavorable to restful sleep (3,5,6) .…”
Section: Introductionmentioning
confidence: 99%
“…(items 9, 10, and 11);(4) sleep anxiety (items 5, 7, 8, and 21); (5) nighttime wakefulness (items 16, 24, and 25); (6) parasomnia (items 12, 13, 14, 15, 17, 22, and 23); (7) SDB (items 18, 19, and 20); and (8) daytime sleepiness (items 26, 27, 28, 29, 30, 31, 32, and 33…”
mentioning
confidence: 99%